2022
DOI: 10.3390/foods11030385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peroxyl Radical-Induced Oxidation on Functional and Structural Characteristics of Walnut Protein Isolates Revealed by High-Resolution Mass Spectrometry

Abstract: The present study aims to investigate the structural and functional properties of oxidated walnut protein isolates (WPI) by 2,2′-azobis (2-amidinopropane) dihydrochloride (AAPH). The oxidation degree, changes in structural characteristics, processing properties, and protein modifications of WPI were measured. The results showed that oxidation significantly induced structural changes, mainly reflected by the increasing carbonyl content, and decreasing sulfhydryl and free amino groups. Moreover, the secondary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Most protein oxidation happens on the side chain of amino acid residues. Oxidation can result in structural modifications to proteins, such as aromatic hydroxylation, sulfhydryl oxidation, and carbonyl formation ( 47 ). Frequently, alterations in the muscle fiber structure of meat products are the result of heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Most protein oxidation happens on the side chain of amino acid residues. Oxidation can result in structural modifications to proteins, such as aromatic hydroxylation, sulfhydryl oxidation, and carbonyl formation ( 47 ). Frequently, alterations in the muscle fiber structure of meat products are the result of heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that oxidation treatment could significantly increase the carbonyl group, reduce the sulfhydryl group, change the secondary structure, and increase the foaming and water/oil holding capacity of protein. 63 Chemical phosphorylation modification can improve the functional properties of proteins by changing their internal structures and surface properties. Generally, the mechanism of phosphorylation modification is based on the introduction of phosphate groups into the side chains of amino acid residues to increase the electronegativity of proteins and then affects their functional properties.…”
Section: Functional Properties Of Walnut Proteinmentioning
confidence: 99%
“…Zhang et al studied the effect of water-soluble radical initiator 2,2′-azobis (2-amidinopropane) dihydrochloride (AAPH) to oxidize WP on the structural and functional properties of the protein. The results showed that oxidation treatment could significantly increase the carbonyl group, reduce the sulfhydryl group, change the secondary structure, and increase the foaming and water/oil holding capacity of protein . Chemical phosphorylation modification can improve the functional properties of proteins by changing their internal structures and surface properties.…”
Section: Functional Properties Of Walnut Proteinmentioning
confidence: 99%
“…However, moderate oxidative modification could promote the partial unfolding of rice bran protein and improve its water retention and emulsification (Wu et al ., 2020a). Besides, the foaming and water‐holding capacity of walnut protein were also improved to varying degrees after oxidation (Zhang et al ., 2022c). Metal‐catalysed oxidation of pea protein increased the aggregation stability of the droplets during emulsification, and the structural interface of pea protein milk was more uniform (Hinderink et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%